(untitled) (Pravaha, 2018)
The main purpose of this research is to examine the relationships among trust, justice and organizational commitment at hospitals in Nepal. The success of an organization is closely relatedto its employees’ perception of trust, and justice within the organization. This study is based on the effect of perceptions of trust in management and organizational commitment among the nurses working in different hospital at Kathmandu Valley. This study includes the design and distribution of a self-administered questionnaire to 465 nurses belonging to different hospitals working on different basic pay scales.This paper is useful to academicians and organizations to understand the level of relationship that will help them to manage the organization in accordance with its objectives. Improved treatment of organizational and developing mutual trust and understanding between management and workers lead to the organizational commitment. Pravaha Vol. 24, No. 1, 2018, Page: 31-38